2015
DOI: 10.1080/21597081.2015.1080787
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel phage lysin active againstPaenibacillus larvae, a honeybee pathogen

Abstract: Paenibacillus larvae is the causative agent of American foulbrood (AFB) disease which affects early larval stages during honeybee development. Due to its virulence, transmissibility, capacity to develop antibiotic resistance, and the inherent resilience of its endospores, Paenibacillus larvae is extremely difficult to eradicate from infected hives which often must be burned. AFB contributes to the worldwide decline of honeybee populations, which are crucial for pollination and the food supply. We have isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
(58 reference statements)
1
17
0
2
Order By: Relevance
“…Given that a tail tape measure protein was identified in all P. larvae phage genomes, and a major tail protein in almost all genomes, and that in all such instances there are only two genes between the major tail protein and the tape measure protein, we assigned tail assembly function to these two genes. This was further confirmed when we identified a translational frameshift between these genes, as is commonly found in tailed bacteriophages [ 20 , 21 , 22 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Given that a tail tape measure protein was identified in all P. larvae phage genomes, and a major tail protein in almost all genomes, and that in all such instances there are only two genes between the major tail protein and the tape measure protein, we assigned tail assembly function to these two genes. This was further confirmed when we identified a translational frameshift between these genes, as is commonly found in tailed bacteriophages [ 20 , 21 , 22 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 79%
“…A N -acetylmuramoyl- l -alanine amidase has been identified in all P. larvae phage genomes. This is the most studied P. larvae phage protein, being the subject of at least two studies, and the only P. larvae phage protein whose function has been experimentally verified [ 22 , 25 ]. It is the chief gene responsible for lysing P. larvae, by cleaving its peptidoglycan cell wall [ 22 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last year alone 5 studies were published on treating AFB with P. larvae phages or P. larvae phage endolysins, with promising, if not conclusive, results. 19-23 …”
Section: Introductionmentioning
confidence: 99%
“…In vivo safety tests confirmed that it was not toxic. Le Blanc et al (2015) isolated lysin PlyPAlA with amidase activity from the genome of P. larvae phage Xenia ( Le Blanc et al, 2015 ). Higher enzyme activity in vitro was observed against P. larvae strain with genotype ERIC I compared to ERIC III and IV.…”
Section: Phage Application Potentialmentioning
confidence: 99%